Plasma modification of textiles: understanding the mechanisms involved. Issue 4 (2nd October 2018) - McCoustra, M. R. S.; Mather, R. R.
Abstract: Plasma treatments are acquiring growing commercial recognition as a highly practical means of altering the surface properties of textiles without detriment to their bulk properties. It is clearly desirable that processing conditions are formulated as accurately as possible, so that fewer trials are required to achieve a desired outcome. We discuss how better formulation is achievable from a clearer understanding of the mechanisms comprising the plasma process. This improved understanding comes from not only analysing surface chemical and topographical changes resulting from a plasma treatment, but also monitoring key processes taking place during the treatment. Furthermore, we highlight the application of computational approaches, statistical experimental design and process control as supporting tools and highlight the role that artificial intelligence may play in the future. We also consider three specific plasma treatments of textiles and propose how examples of these approaches extracted from the literature may be combined, to achieve more realistic formulations.